(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
The constituent process in which Chile is currently engaged has opened a new phase in the history of the Latin American nation. On the table, in fact, there is not “only” the adoption of a new constitution, but a fundamental pillar of the dictatorial legacy. Legacy that calls into question the profound lacerations produced by the extremely complex civic-military regime, which guided the country from 1973 to 1990, as well as the limits, contradictions and complicities of the period of democratic governments.